Histopathological assessment of the microscopic activity in inflammatory bowel diseases: What are we looking for? - Fabian, Ondrej; Bajer, Lukas (World journal of gastroenterology, 2022)
Advances in diagnostics of inflammatory bowel diseases (IBD) and improved treatment strategies allowed the establishment of new therapeutic endpoints. Currently, it is desirable not only to cease clinical symptoms, but mainly to achieve endoscopic remission, a macroscopic normalization of the bowel mucosa. However, up to one-third of IBD patients in remission exhibit persisting microscopic activity of the disease. The evidence suggests a better predictive value of histology for the development of clinical complications such as clinical relapse, surgical intervention, need for therapy escalation, or development of colorectal cancer. The proper assessment of microscopic inflammatory activity thus became an important part of the overall histopathological evaluation of colonic biopsies and many histopathological scoring indices have been established. Nonetheless, a majority of them have not been validated and no scoring index became a part of the routine bioptic practice. This review summarizes a predictive value of microscopic disease activity assessment for the subsequent clinical course of IBD, describes the most commonly used scoring indices for Crohn's disease and ulcerative colitis, and comments on current limitations and unresolved issues.
Keywords: střevní sliznice; idiopatické střevní záněty; Crohn Disease; ulcerózní kolitida; Predictor; Microscopy; Crohnova nemoc; Humans; endoskopie; Inflammatory Bowel Diseases; Ulcerative colitis; Intestinal Mucosa; Crohn’s disease; Colitis, Ulcerative; lidé; Score; Endoscopy